Relationship Between the ApaI (rs7975232), BsmI (rs1544410), FokI (rs2228570), and TaqI (rs731236) Variants in the Vitamin D Receptor Gene and Urolithiasis Susceptibility: An Updated Meta-Analysis and Trial Sequential Analysis - Chen, Guangyuan; Hu, Cong; Song, Yuxuan; Xiu, Mengxi; Liang, Wanfeng; Ou, Ningjing; Liu, Xiaoqiang; Huang, Peng (Frontiers in Genetics, 2020)
Abstract Relationship between urolithiasis and vitamin D receptor (VDR) gene variants is still under debate according to available published literature. To assess correlations between VDR gene ApaI (rs7975232), BsmI (rs1544410), FokI (rs2228570) and TaqI (rs731236) variants and urolithiasis susceptibility, we performed the present study through meta-analysis. PubMed, Cochrane Library, China National Knowledge Infrastructure, EMBASE, Web of Science, and Wanfang databases were retrieved to collect qualified case-control studies. Finally, 31 reports were selected into the present meta-analysis. Results demonstrated that VDR gene TaqI TT genotype was related to the decreased risk of urolithiasis in overall population (TT vs. Tt+tt: P=0.011, OR=0.824, 95%CI=0.709–0.957). In ethnicity subgroup analysis, we found TaqI variant was obviously correlated to urolithiasis risk among Asians and Caucasians (P<0.05). Besides, significant urolithiasis risk was identified in adults. However, FokI, BsmI and ApaI variants did not have an increased risk of developing urolithiasis. Trial sequential analysis results were in a sufficiently large number of participants and did not require more researches to confirm such association. Our research suggested that VDR gene TaqI variant was correlated with urolithiasis susceptibility and t-allele might be the risk gene and T-allele might be the protective gene in VDR TaqI variant.